Finalna obróbka krzemiennych siekier i narzędzi siekieropodobnych. Studium eksperymentalne - Kubicki, Radosław Ł. (Folia Praehistorica Posnaniensia, 2015)
This article discusses the final processing of flint axes and wedge-shaped tools. The author in his considerations focuses primarily on the use of two hypothetical processes, i.e. hand grinding or grinding with extra weight at the final stage of manufacturing these tools. Thus, he refers to the work by Danish archaeologist B. Madsen of 1984, entitled “Flint Axe Manufacture in the Neolithic: Experiments with Grinding and Polishing of Thin-Butted Flint Axes”, in which the researcher discussed, for the first time, an occurrence of these techniques in the axe-production process. The author of the article makes an attempt to repeat Madsen’s achievements, to check validity of the concept, and to include also an issue of using so called abrasive materials to support a grinding process in prehistory.